Educated experts jurists are necessary to the eternal constitutional state. (Journal of actual problems of jurisprudence, 2016)
In article methods of increase of level of legal education of students of higher educational an institution are considered.A number of suggestions for improvement of legal education in the Republic of Kazakhstan is offered. Legal education is a sign of activity of government bodies and public association which forms legal culture and consciousness of society. The more, the state will pay special attention in development of legal education of citizens, the more legalconsciousness and legal culture will be top-level. Because, the legal consciousness, culture, legal science is a source of an order and discipline.
Keywords: legal education; legal awareness; legal science; legal culture